PURPOSES AND METHODS OF ACCOUNTING INSTRUCTION. - Tupy, L. P. (The Accounting Review, 1927)
Abstract The purposes of accounting instruction in universities and colleges, although manifold and dependent upon innumerable circumstances, may be grouped into two major classifications. These two classifications are the social purposes and the private purposes. Some might point out a third group of purposes, that is, those growing out of the needs of particular institutions as affected by their character and location, but ordinarily these latter facts merely influence the social and private purposes and do not form a third group. Of the two groups, the social purposes should be considered the more important. To bring out the social function of the subject should be the most important purpose of accounting instruction. Accounting instruction not only serves the two private purposes, the vocational and professional, directly, but it has an additional private purpose. The accounting instruction is a foundation stone in any course in commerce or business administration. Thus persons enrolling in a commerce course, and whose ambition is to become business men, partake of this instruction and can use it later to their own individual advantage.